2005
DOI: 10.1080/15412550500218122
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Obstructive Pulmonary Disease in Finland: Prevalence and Risk Factors

Abstract: Background and Aim: Normal spirometric values and prediction equations are largely unknown for Tibet residents. This study aimed to determine spirometric values and establish prediction equations for healthy Tibet residents. Methods: This prospective cross-sectional study enrolled 2909 healthy, non-smoking Tibetans aged 15-98 years. A multistage cluster sampling strategy was used for sample selection. Anthropometric and spi-rometric data from six different urban and rural areas were obtained. Age stratificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
53
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 41 publications
8
53
2
Order By: Relevance
“…Since there are only a few available epidemiological studies on the prevalence of COPD in Finland, 9,17,18 and given that our follow-up period was relatively short, no reduction in COPD prevalence could be detected between 1997 and 2007. However, according to a recent study, the prevalence of COPD has not changed significantly in Finland between 1980 and 2001, 10 reflecting the possible long-term change in smoking habits in both genders; in the 1950s, 75% of men and 10% of women smoked, but in the 1990s only 30% of men and 20% of women smoked (www.thl.fi).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since there are only a few available epidemiological studies on the prevalence of COPD in Finland, 9,17,18 and given that our follow-up period was relatively short, no reduction in COPD prevalence could be detected between 1997 and 2007. However, according to a recent study, the prevalence of COPD has not changed significantly in Finland between 1980 and 2001, 10 reflecting the possible long-term change in smoking habits in both genders; in the 1950s, 75% of men and 10% of women smoked, but in the 1990s only 30% of men and 20% of women smoked (www.thl.fi).…”
Section: Discussionmentioning
confidence: 99%
“…9,10 The first study, published in 2005, 9 estimated the prevalence of COPD in 1995-1996 based on GOLD criteria and Finnish reference values, and the second study evaluated COPD prevalence between the years 1978-1980 and 2000-2001. 10 The follow-up periods of these studies did not cover the entire span of the 10-year Programme (which ended in 2007), but they did assess prevalence over a relatively long, 20-year period.…”
Section: Epidemiologymentioning
confidence: 99%
“…21 In our study, the majority of people with COPD were male, while most of the people with chronic bronchitis were female. Many studies [22][23][24][25] have reported that a low socioeconomic level, as measured by education, income or other indices of social class, is a risk factor for COPD. Our results support this finding.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies on the prevalence of COPD [11,[26][27][28] and its trends over the course of time [29,30] have been confined to certain communities or areas within a country. Few studies have been based on wider representative study populations [31,32], but even then only one single study has been carried out.…”
Section: Discussionmentioning
confidence: 99%